PRIVATISASI PENYALURAN TENAGA KERJA INDONESIA: MASIHKAH BERMANFAAT? - Samodra Wibaswa; Dewi Sekar Tanjung; Ahmad Iqbal (Populasi, 2003)
The management of migrant workers was privatized in 1983, ostensibly because the private sector was thought to be more resilient to do the job. Consequently, there was a drastic increase in the number of migrant labor sent abroad, which was not short of mishaps, among which were: abandonment of migrant workers, cheating, holdups, sexual harassment and death. In the backdrop of such effects various suggestions on how to foster improvements, which should include among others: contracts between the workers andfirms, and the provision of insurance to the migrant workers. In addition, job seekers must be given detailed information on their rights and responsibilities and the merits and demerits of working in a certain country, and the government must make agreements with countries that are the destinations of the workers. The Ministry for labor and transmigration perhaps should increase the size of its bureaucracy to take up the roles that will be relinquished by the private sector. It is no longer debatable that government officials have shown over the last2few years that they can live to the spirit and latter of the entrepreneur, far beyond the achievements of the private sector.